Mekanisme Penetapan Harga Jual Beli Hasil Pertanian Dalam Persfektif Ekonomi Islam di Kabupaten Aceh Utara - Fuadi, Fuadi; Marliyah, Marliyah; Falahuddin, Falahuddin; Mutia, Intan (Jurnal EMT KITA, 2021)
The purpose of this study is to see that farmers provide for their family's needs with the rice yields obtained for each harvest. But lately, farmers have felt that there are problems that occur from the sale of rice harvests, because lately agents have set sales prices unfairly. This study uses qualitative research with data collection techniques by observation, interviews and documentation. The results of the study found that the mechanism for determining the sale and purchase price of agricultural products in the form of rice by agents to farmers in Muling Manyang Village in general could not be said to be good because most of the rice agents had not applied prices in accordance with sharia economic principles, only a few parties set prices in accordance with Islamic economic perspective.